3D-Printable and open-source modular smartphone visible spectrophotometer. (October 2021) - Winters, Brandon J.; Banfield, Nick; Dixon, Cassandra; Swensen, Anna; Holman, Dakota; Fillbrown, Braxton
Graphical abstract: Abstract: The past four decades have brought significant and increasingly rapid changes to the world of instrument design, fabrication, and availability due to the emergence of 3D printing, open-source code and equipment, and low-cost electronics. These, along with other technological advances represent a nexus in time ripe for the wide-spread production and availability of low-cost sophisticated scientific equipment. To that end, the design of a 3D printable and open-source, modular spectrometer is described. This specific instrument is distinctly different from others that have been reported in recent years in that it was designed outside of the "black box" paradigm of nearly all other commercially available and open-source spectrometers. This feature along with its design to be produced on low-end consumer-grade 3D printers and with parts available at nearly any local hardware store allow this instrument to further erode current barriers to instrument access. Additionally, the use cases presented here demonstrate similar capabilities to commercially available equipment at a fraction of the cost.